HUBUNGAN FAKTOR KETURUNAN, USIA DAN OBESITAS TERHADAP KEJADIAN HIPERTENSI PADA IBU HAMIL DI PUSKESMAS PAAL MERAH I KOTA JAMBI TAHUN 2016 - Ruwayda Ruwayda (Poltekkes Kemenkes Jambi, 2016)
Hypertension is blood pressure at the upper limit of normal, hypertension included in a globalproblem that is sweeping the world. Hypertension in pregnancy is 5-15 complication of pregnancy and isone of the top three causes of maternal mortality and morbidity. Data Jambi City Health Department in2013, the incidence of hypertension in pregnancy as many as 66 people (2.27%), the highest number ofpeople with hypertension are at Puskesmas Paal Merah I were 19 pregnant women (22.09%). In 2014 asmany as 141, or approximately 4.83% of pregnant women, the highest rates are in Puskesmas Paal MerahI were 22 pregnant women (18.18%). Then in 2015 the highest rate found in Puskesmas Paal Merah I asmany as 16 people (17%).This research is descriptive analytic cross sectional approach to determine the frequencydistribution relationship Heredity, age and obesity with the incidence of Hypertension in Pregnancy HealthCenter Paal Merah I Jambi City Year 2016. The respondents are pregnant women who visited the healthcenter I Paal Merah Jambi city. The population in this study 142 people, and the sample in the study of 33pregnant women. Sample selection is done with accidental sampling technique. The data was collectedthrough interviews, measurements of blood pressure, height measurement by means of data collectionthrough the sheet questionnaires, the data were analyzed by univariate and bivariate with chi square test.The results showed as many as 11 respondents (33.3%) suffered from hypertension inpregnancy, as many as 15 respondents (45.5%) had hypertension descent, as many as 14 respondents(42.4%) had a risk for hypertension age, as many as 14 respondents (42, 4%) suffer from obesity. There is a link between inheritance (0000) age (0.000) and obesity (0.000) and the incidence of hypertension inpregnant women at health centers Paal Merah I Jambi 2016.Counseling needs to be done on the mother's pregnancy when the limit is entering the ageof risk, then, in trying to pregnancy does not occur at ages under 20 years, so it could be at risk ofhypertension. Additionally mothers who became pregnant at the risk must pay attention to things that cancause hypertension, such as a history of hypertension and reduce the descendants of salt in food.